Strategy for the Development of Superior Potential of the Agriculture and Plantation Sector in Tambrauw Regency - Nasrullah, Muh.; Arhas, Sitti Hardiyanti; Iskandar, Didik (PINISI Discretion Review, 2025)
The development of the agricultural and plantation sectors in Tambrauw Regency is an urgent need considering the high biodiversity of the region which has not been followed by the availability of infrastructure, agricultural technology, and adequate market access. This study aims to formulate a strategy for developing regional superior potential that is able to connect ecological forces, structural challenges, downstream opportunities, and natural resource conservation needs. The study method was carried out through sequential stages ranging from preliminary preparation and seminars, primary and secondary data collection, cross-sector Focus Group Discussions, to potential analysis and clustering of areas validated through final seminars with local governments. The results of the study show that the acceleration of the development of the agricultural sector in Tambrauw requires an integrated strategy that includes the use of biodiversity for the creation of superior products, improving production infrastructure and technology, optimizing downstream programs to increase added value, and using digital media to expand market reach. This approach provides a foundation for the development of a more productive, inclusive, and sustainable local resource-based regional economy.